Electrical Impedance Measurements in the Reading and Monitoring of Broth Dilution Susceptibility Tests - Colvin, H. J. (1977)
Electrical impedance changes in the medium were studied during traditional broth dilution tests. Tests involved clinical isolates of Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Enterobacter sp., Klebsiella, and enterococcus and ten antibiotics. Minimal inhibitory concentration (MIC) values from overnight visual readings were compared with MIC values determined from electrical impedance end points, using inocula of 10(6) organisms per ml. Ninety-three percent of the results were within one twofold dilution of each other. When the impedance end point was determined at 6 h, this correlation was lowered to 34%. By increasing the initial electrical impedance inoculum 10-fold, the correlation between the 6-h impedance MIC and the overnight visual MIC was improved to 74%. Ampicillin, tetracycline, and polymyxin E results accounted for most discrepancies. Continuous monitoring of impedance changes suggested that better correspondence could be obtained by adjusting the end point criteria for the 6-h impedance MIC with different antibiotics. Electrical impedance methods for reading bacterial end points in automated clinical laboratory instruments appear promising.